1980
DOI: 10.1073/pnas.77.6.3417
|View full text |Cite
|
Sign up to set email alerts
|

Serum factors modify the cellular requirement for Ca2+, K+, Mg2+, phosphate ions, and 2-oxocarboxylic acids for multiplication of normal human fibroblasts.

Abstract: The rate of multiplication of a population of cultured human lung fibroblasts is determined by the level of common nutrients and serum factors in the medium. By application of the principles of Henri-Michaelis-Menten kinetic analysis to cell growth in vitro, the relationship between the level of a macromolecular fraction of serum that contains growth factors and the concentration of individual nutrient that is required to support a half-maximal rate of cell multiplication was explored. The requirement for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1981
1981
1986
1986

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Nevertheless, PC is still quite effective in replacing HDL for relatively short-term growth. McKeehan and McKeehan (1980) recently suggested that PC i s one of the extracellular nutrients most likely to be involved in the mechanism by which serum growth factors control cell multiplication. Consistent with this hypothesis are the recent reports linking membrane phospholipid synthesis, in particular that of PC, to DNA synthesis (Hirata and Axelrod, 1980) and passage through the cell cycle (Cornell and Horwitz, 1980).…”
Section: Pcmentioning
confidence: 99%
“…Nevertheless, PC is still quite effective in replacing HDL for relatively short-term growth. McKeehan and McKeehan (1980) recently suggested that PC i s one of the extracellular nutrients most likely to be involved in the mechanism by which serum growth factors control cell multiplication. Consistent with this hypothesis are the recent reports linking membrane phospholipid synthesis, in particular that of PC, to DNA synthesis (Hirata and Axelrod, 1980) and passage through the cell cycle (Cornell and Horwitz, 1980).…”
Section: Pcmentioning
confidence: 99%
“…Growth factors may change multiplication rate by causing a change in the cellular requirement (So.so value) for a nutrient that is analogous to a change in the K, of an enzyme for its substrate. To examine for this, we applied the kinetic approach to relate simultaneously the level of FBSP or other growth factors and the level of individual nutrients in the medium to cell multiplication rate [19,20,23,[33][34][35][36]. Three different types of relationships were observed between FBSP and individual nutrients (Figs.…”
Section: Modification Of Nutrient Requirements By Serum Growth Factorsmentioning
confidence: 99%
“…Although some lipids 1301, niacinamide 1291 and the ions of Fe and Se showed class I and I1 relationships with FBSP, a functional modification of their requirement in multiplication by FBSP could not be distinguished from their addition to deficient culture medium as a contaminant in the FBSP [35]. Table I1 summarizes the classification of all the nutrients tested.…”
Section: Modification Of Nutrient Requirements By Serum Growth Factorsmentioning
confidence: 99%
See 2 more Smart Citations